Microstructure and mechanical properties of asextruded Mg–xAl–5Sn–0·3Mn alloys (x = 1, 3, 6 and 9). (February 2015) - She, J.; Pan, F.; Peng, P.; Tang, A.; Yu, Z.; Wu, L.; Pan, H.; Zhao, C.; Gao, Z.; Luo, S.; Rashad, M.
<x content-type="archive" xml:space="preserve">Abstract</x> Properties of Mg–xAl–5Sn–0·3Mn alloys (x = 1, 3, 6 and 9) prepared by hot extrusion are reported. The orientation relationship between Mg2Sn precipitate and Mg matrix in Mg–9Al–5Sn–0·3Mn alloy was determined. The yield strength of the as extruded alloys initially decreased with increasing Al content, then increased for Al contents >6 wt-%. These changes are interpreted in terms of the effect of texture, grain size and second phase on the yield strength of the alloys.